Corrosion Testing of Casing Materials for Carbon Dioxide Reinjection Wells - Gaël Horner 1992- (2023)
Carbon dioxide storage in basaltic reservoirs is conducted through re-injection in geothermal wells by mixing sourced carbon dioxide with geothermal brine. In order to implement it, there is a need to identify best suitable material for transport and storage systems. The object of this study is to recreate operational conditions in an autoclave in order to assess corrosive effects on 5 candidate materials for implementation. Conditions were recreated in the Material and Corrosion Laboratory at University of Iceland autoclave chamber by mixing sourced geothermal brine with dissolved and gaseous CO2 under conditions expected in the well. 1 carbon steel and 4 stainless steel type samples were exposed to the fluid for an extend period of time. Corrosion damages were assessed with weight loss analysis, and microstructural and chemical composition analysis with Scanning Electron Microscope (SEM) equipped with Energy-Dispersive X-ray Spectroscope (EDS). In summary the results showed that the stainless steel sample 1,2 and 3 did not saw any damages but some corrosive products deposits on their surface has been observed, while stainless steel sample 1 suffered minor weight loss. Carbon steel sample, meanwhile, suffered way higher weight loss than other samples. It also showed major pits and cracks formation on its surface.